Análise em livros didáticos dos anos finais do ensino fundamental sobre o conteúdo de geometria - NASCIMENTO, Maiza Rodrigues de Sousa (Universidade Federal do Tocantins, 2023)
This study presents a study focused on the approach and development of the existing Geometry content in the Mathematics textbooks of the Final Years of Elementary Education (EF), published in the years 2015 and 2018. To this end, we conducted an approach study qualitative of the type of bibliographic research and of a descriptive character, based on the National Common Curricular Base (BNCC), the National Textbook Program (PNLD) and the National Curricular Parameters of Mathematics (PCN) of Mathematics. From the reflective readings on these documents we have that, Geometry has an important role in the student's life, with its most varied forms and concepts perceptible in all educational stages. In this educational perspective, this work sought to analyze the presence of this content in textbooks, verifying whether the units or chapters destined to Geometry, present a direct or indirect relationship with the BNCC document, and the problematic questions of the investigation were: 1st) In LD it is possible to find historical facts in the theoretical explanation of the content? 2a) Are the figures presented in the LD consistent with the discursive treatment? 3rd) Do the LDs present indications of the use of technology for the teaching of Geometry? As a result, the analyzed books indicate that the content of Geometry is described in the form proposed by the BNCC, highlighting its didactic, pedagogical and methodological potential in the course of teaching the thematic units, skills and objects of knowledge, in addition to pedagogical indications to resize the planning of the teacher, in particular the teacher who teaches mathematics, in public schools of Basic Education.